RECREATIONAL AND HEALTH WORK IN A HIGHER EDUCATIONAL INSTITUTION FOR PSYCHO-EMOTIONAL CORRECTIO OF STUDENT YOUTH (Physical Culture and Sport: Scientific Perspective, 2025)
The relevance of the research topic lies in determining the main motives of higher education students for recreational and health activities and finding ways to improve the psycho-emotional state of student youth. The article considers the problematic issues of psycho-emotional correction of negative psychological states of student youth by means of extracurricular recreational and health work in a sports camp. Purpose: analysis of the readiness of the sports and health facilities of higher education institutions of the Dnipro region for recreational and health activities; study of the impact of recreational and health methods on the psycho-emotional state of student youth in the conditions of the Priorilskyi Nature Reserve. Methods: psychological and pedagogical observation; questionnaires; methods of psychological diagnostics; physiological methods (pulsometry, tonometry, functional tests); methods of motor tests. Results: The psychological and pedagogical research was conducted in stages: the first stage is organizational; the second stage is practical; the third stage is control and evaluation. The effectiveness of the process of correcting the psycho-emotional state of higher education applicants can be increased if psychological and pedagogical conditions are implemented. Recreational and health-improving techniques are designed to have a comprehensive impact on the psycho-emotional state of student youth through the use of various types of physical activity (health-improving exercises, sports games, hiking, walking, etc.), methods of psychological influence (verbal and figurative emotional and volitional management of a person's condition, breathing exercises), phytotherapy and the use of mineral water. According to the research hypothesis, natural factors combined with health and physical activity should have a positive impact on the psycho-emotional state of young students. In the course of the conducted research, it can be stated that the proposed method of psycho-emotional correction of negative states of student youth using health and recreational practices is effective both in improving the psycho-emotional state and physical training, and in indicators of functional state, contributes to the formation of a healthy lifestyle, and increases motivation for physical education. Our research allows us to assert that recreational and health-improving classes with students, which are conducted using special methods, have an important health-improving value.
Keywords: student youth; health; psycho-emotional correction; physical culture; personality